Knowledge mapping of exosomes in preeclampsia: a bibliometric analysis (2008-2023) - Yin, Liang; Zhang, Yuchao; Fu, Guanfeng; Huang, Haiqin; Su, Hang; Zhang, Yipeng; Chen, Qichun; Li, Qinghua; Yang, Weiwei (Frontiers in Endocrinology, 2025)
BackgroundExosome research in preeclampsia is gaining increasingly popular, however thorough and unbiased summaries of the field’s present understanding are hard to come by. Therefore, this study aims to conduct a bibliometric analysis of the publication “Exosomes in Preeclampsia” in order to visually analyze the state of the field and identify emerging trends.MethodsFrom 2008 to 2023, the Web of Science database was searched for publications related to exosomes in preeclampsia. Three software packages—VOSviewer, CiteSpace, and the R program “bibliometrix”—were used to conduct bibliometric analysis.ResultsAnalysis of 257 publications produced by 1454 scholars from 48 countries/regions and 435 institutions, published in 135 academic journals. The quantity of studies concerning exosomes in preeclampsia is steadily increasing. China and the United States lead in publications, with Oxford being the most active university. Placent has written the most relevant study and has received the highest number of citations. Carlos Salomon has the most number of published articles and is the most referenced author. The 10 most frequently mentioned sources were used as a knowledge basis. The predominant terms examined include extracellular vesicle, expression, pregnancy, microparticle, and microRNA. Utilizing fundamental research on exosomes in preeclampsia for clinical diagnosis and therapy is a current popular research focus and direction. Utilizing fundamental research on exosomes in preeclampsia for clinical diagnosis and treatment is currently a popular research focus and direction.ConclusionThis study offers a comprehensive overview of trends and advancements in the research of exosomes in preeclampsia through bibliometrics. This material highlights the current research frontiers and trending directions, serving as a valuable reference for researchers in the subject.